Bach Flower Remedies - Ball, Stefan (London : Teach Yourself, 2000)
This guide to the 38 Bach flower essences provides information on which ones to select, and how they can be used to control and balance your emotions. The book is endorsed by both the Bach Centre and the Bach International Education Programme.
Includes bibliographical references (p. 187) and index.
Keywords: Flowers -- Therapeutic use; Materia medica, Vegetable; Health and Fitness